Highly Conducting, Transparent PEDOT:PSS Polymer Electrodes from Post‐Treatment with Weak and Strong Acids. (3rd January 2019) - Bießmann, Lorenz; Saxena, Nitin; Hohn, Nuri; Hossain, Md Asjad; Veinot, Jonathan G. C.; Müller‐Buschbaum, Peter
Abstract: The origin of high conductivity in polymer electrodes based on poly(3, 4‐ethylene dioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) is investigated and the resilience against water exposure is tested. Post‐treatment with weak and strong acids, namely, hydrochloric acid (HCl), formic acid (HCOOH), nitric acid (HNO3 ), and sulfuric acid (H2 SO4 ), is performed and compared to the commonly used ethylene glycol treatment. PEDOT:PSS electrodes with electrical conductivities of up to ≈3000 S cm −1 and high transmittance are obtained. The underlying mechanisms for enhanced conductivity are elucidated by means of electrical (4‐point probe), optical (UV‐Vis spectroscopy), compositional (X‐ray photo‐electron spectroscopy), and structural (grazing‐incidence wide‐angle X‐ray scattering, GIWAXS) characterizations. Selective PSS removal and structural rearrangement of PEDOT‐rich domains due to an enhanced lamellar stacking is identified as major influence on the improvement in electrical conductivity. This beneficial high order is evidenced via additional signals in the GIWAXS patterns, which are altered by subsequent H2 O treatment. The PSS removal and structural rearrangement is linked to the acids' strength and dielectric constant. High conductivities are reached by efficient PSS removal via HNO3 or H2 SO4 treatment with the drawback of high sensitivity against H2 O. By contrast, HCl and HCOOH treatment obtaining a medium enhanced conductivity differ in the amount of PSS removal but show higher H2 O resistance. Abstract : PEDOT:PSS polymer electrodes are studied upon impact of weak and strong acid treatments. In order to investigate compositional and structural changes, XPS and GIWAXS are used. Changes in transparent electrode performance are linked to acids' strength and Coulomb screening ability of the used solvents. High degree of lamellar stacking is found to be effective for high electrode performance.